2000
DOI: 10.1177/1368430200003002004
|View full text |Cite
|
Sign up to set email alerts
|

A Dynamic Model of Group Performance: Considering the Group Members’ Capacity to Learn

Abstract: A dynamic model of group performance is suggested that combines the group learning approach and the combination of contributions approach. Three hypotheses are tested in two experiments, comparing individual training conditions with mixed group and individual training conditions on subsequent nominal and collective group performance of rule induction tasks under identical time constraints. As predicted, collective group performance improves as a function of group experience, nominal group performance improves … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
36
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 62 publications
3
36
1
Order By: Relevance
“…For instance, using the very same probability judgment paradigm, Argote, Seabright, and Dyer (1986) showed that group judgments are less affected by base-rate information than judgments made by individuals; whereas Argote, Devadas, and Melone (1990) showed that sometimes group judgments are more sensitive to base-rates than individual judgments. This not-isolated example of mixed findings points to the fact that the search for a single answer to the question of whether N þ 1 heads are indeed better than one (see Hill, 1982) may be less productive, both socially and empirically, than the search for answers to the questions of when and why groups perform differently (i.e., better and worse) than individuals (see, e.g., Broadbeck & Greitemeyer, 2000;Kerr et al, 1996 for similar reasoning). In this spirit, the present paper examines when groups perform differently from individuals in the Wason selection task (Wason, 1966) and attempts to shed some light on why any such differences occur.…”
mentioning
confidence: 92%
“…For instance, using the very same probability judgment paradigm, Argote, Seabright, and Dyer (1986) showed that group judgments are less affected by base-rate information than judgments made by individuals; whereas Argote, Devadas, and Melone (1990) showed that sometimes group judgments are more sensitive to base-rates than individual judgments. This not-isolated example of mixed findings points to the fact that the search for a single answer to the question of whether N þ 1 heads are indeed better than one (see Hill, 1982) may be less productive, both socially and empirically, than the search for answers to the questions of when and why groups perform differently (i.e., better and worse) than individuals (see, e.g., Broadbeck & Greitemeyer, 2000;Kerr et al, 1996 for similar reasoning). In this spirit, the present paper examines when groups perform differently from individuals in the Wason selection task (Wason, 1966) and attempts to shed some light on why any such differences occur.…”
mentioning
confidence: 92%
“…In other words, multiple group interactions did not affect the strength of the individual performance enhancements. However, all of these studies worked with tasks that are very likely characterized by high levels of demonstrability, which is considered to be a prerequisite for the occurrence of G-I transfer (Brodbeck & Greitemeyer, 2000a). According to Laughlin and Ellis (1986), one of the core conditions of demonstrability is that the member with the correct answer must have the ability, motivation, and time to demonstrate the correct solution to the other group members.…”
mentioning
confidence: 99%
“…As already mentioned, this socially induced individual learning is known as G-I transfer. Examples of such learning processes are vicarious learning, or exchange of basic principles and strategies for effective task performance (e.g., Laughlin & Jaccard, 1975;Brodbeck & Greitemeyer, 2000a, 2000b.…”
mentioning
confidence: 99%
“…However, it is possible that further opportunities for exchange and collaboration for participants under the unshared condition would have allowed them to benefit from their heterogenous knowledge to a further extent. As groups working together over a longer period of time and coming together on several occasions can learn more over time (Brodbeck & Greitemeyer, 2000), further studies should examine the reported effects in a longitudinal setting.…”
Section: Discussionmentioning
confidence: 99%